Demographic, Reproductive, and Medical Risk Factors for Intrauterine Device Expulsion. Issue 6 (2nd December 2022) - Anthony, Mary S.; Zhou, Xiaolei; Schoendorf, Juliane; Reed, Susan D.; Getahun, Darios; Armstrong, Mary Anne; Gatz, Jennifer; Peipert, Jeffrey F.; Raine-Bennett, Tina; Fassett, Michael J.; Saltus, Catherine W.; Ritchey, Mary E.; et al.
Abstract : Of the risk factors evaluated, intrauterine device expulsion risk was highest among individuals with chronic, persistent heavy menstrual bleeding. Abstract : OBJECTIVE: To explore to what extent intrauterine device (IUD) expulsion is associated with demographic and clinical risk factors. METHODS: The APEX-IUD (Association of Perforation and Expulsion of IntraUterine Devices) study was a U.S. cohort study using electronic health records from three integrated health care systems (Kaiser Permanente Northern California, Southern California, and Washington) and a health care information exchange (Regenstrief Institute). These analyses included individuals aged 50 years or younger with IUD insertions from 2001 to 2018. Intrauterine device expulsion cumulative incidence and incidence rates were estimated. Using Cox regression models, hazard ratios with 95% CIs were estimated before and after adjustment for risk factors of interest (age, race and ethnicity, parity, body mass index [BMI], heavy menstrual bleeding, and dysmenorrhea) and potential confounders. RESULTS: In total, 228, 834 individuals with IUD insertion and no delivery in the previous 52 weeks were identified (184, 733 [80.7%] with levonorgestrel-releasing intrauterine system). Diagnosis of heavy menstrual bleeding—particularly a diagnosis in both recent and past periods—was the strongest risk factor for IUD expulsion. Categories with the highest risk of IUD expulsion within each risk factor included individuals diagnosed with overweight, obesity, and morbid obesity; those in younger age groups, especially among those aged 24 years or younger; and in those with parity of four or more. Non-Hispanic White individuals had the lowest incidence and risk, and after adjustment, Asian or Pacific Islander individuals had the highest risk. Dysmenorrhea was not independently associated with expulsion risk when adjusting for heavy menstrual bleeding. CONCLUSION: Most risk factors for expulsion identified in this study appear consistent with known physiologic factors that affect uterine anatomy and physiology (age, BMI, heavy menstrual bleeding, parity). The increased risk of IUD expulsion among individuals of color warrants further investigation. Intrauterine devices are an effective long-term contraceptive; expulsion is uncommon, but patients should be counseled accordingly. FUNDING SOURCE: Bayer AG. CLINICAL TRIAL REGISTRATION: EU PAS register, EUPAS33461.